Evolutionary history of Nasutitermes kemneri (Termitidae, Nasutitermitinae), a termite from the South American diagonal of open formations - Kohari, Karolina S.; Palma-Onetto, Valeria; Scheffrahn, Rudolf H.; Vasconcellos, Alexandre; Cancello, Eliana M.; Santos, Rafaella G.; Carrijo, Tiago F. (Frontiers in Ecology and Evolution, 2022)
Little is known about the phylogeography of termites in the Neotropical region. Here, we explored the genetic patterns and phylogeographical processes in the evolutionary history of Nasutitermes kemneri, an endemic termite of the South American diagonal of open formations (DOF) formed by the Chaco, Cerrado, and Caatinga phytogeographic domains. We sampled 60 individuals across the three domains of the DOF, and using the mitochondrial genes 16S, COI, and COII, as well as the nuclear gene ITS, evaluated the genetic diversity and divergence time of the populations, along with their genetic structure. The results show a strong genetic and spatial structure within the samples, evidencing the existence of two well-differentiated genetic groups: the Northeastern and the Southwestern populations, which diverged about 2.5 Mya, during the Pliocene-Pleistocene boundary. The Northeastern population, which encompasses Caatinga and northern portions of Cerrado, has an intricate structure and seems to have suffered repetitive retraction-expansion events due to climactic fluctuations during the Quaternary. The Southwestern population, which ranges from central-south Cerrado to the northeast peripherical portions of the Chaco, displays a star-shaped haplotype structure, indicating that this region may have acted as a refugia during interglacial periods.